The involvement of mesolimbic dopaminergic system in ovulation in rat (Rattus norvegicus) - Soedjono Aswin, Soedjono Aswin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Mesolimbic dopaminergic system involvement in the ovulatory process was studied in the immature superovulation rats (Rartus norvegicus). Nucleus ventralis tegmenti (NVT, area A-10) was neurochemically lesioned by stereotaxically placed injection of I Vg 6-hydroxydopamine (6-OHDA) into the brain. Ovarian weight, frequency and rate of ovulation, the number of corpora lutea found in the ovaries, and histologic features of the ovaries were observed.The results of the present experimental study indicate that neurochemical lesion of NVT with 6-OHDA produced a significant (p<0.01) decrease in the ovarian weight, as well as the ovulation rate and the number of corpora lutea found in the ovaries, compared to the shank-operated control and normal control groups. The frequency of ovulation, however, was not affected; it means that all groups of immature rats underwent ovulation. It is interesting to note that the ovulation rate of the lesioned group was suppressed (but not prevented) by about 60% as shown by the decrease in the number of corpora lutea found in the ovaries and in the number of ova per ovulation. Histologic features of the ovaries of the lesioned group performed an inhibition of follicular development as evidenced by the characteristic :features of the induction of polycystic degeneration, beside the decrease in the number of corpora lutea found in the ovaries.It is concluded that mesolimbic dopaminergic system specifically plays a significant role in the regulation of ovulatory process in the immature superovulation rats. Based on the present data it is hypothesized, that lesioning mesolimbic dopaminergic system chemically with 6-OHDA resulted in significant decrease in luteinizing hormone releasing hormone (LHRH) released from hypothalamus, which in turn ensued the decrease in the tonic release of luteinizing hormone (LH), which is known responsible for the development of the ovarian follicles; but it seems that there is a slight suppression in the pulsatile release of LH, which is responsible for the initiation of ovulation.Key Words: nucleus ventralis tegmenti - mesolimbic dopaminergic systenm - 6-hydronydopanine - ovulation - Rattus riorvegicus